2014
DOI: 10.1111/codi.12698
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between magnetic resonance imaging and rigid rectoscopy in the preoperative identification of intra‐ and extraperitoneal rectal cancer

Abstract: RRS is still the main means of assessing the level of a rectal tumour from the anal verge, but MRI has value in determining the level of the tumour in relation to the PR, which cannot be seen on endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…The direct methods achieved the least bias, the highest precision, and the best correlation with rigid sigmoidoscopy among the three methods groups. The majority of previous studies have measured the tumor distance using multiple lines that reflect the anorectal curvature [2,6,[18][19][20][21][22][23][24]29]. However, in our study, the direct methods using a straight line demonstrated the best results; this corroborates the findings by Meylemans et al, who compared measurement methods using a straight line or multiple straight lines [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The direct methods achieved the least bias, the highest precision, and the best correlation with rigid sigmoidoscopy among the three methods groups. The majority of previous studies have measured the tumor distance using multiple lines that reflect the anorectal curvature [2,6,[18][19][20][21][22][23][24]29]. However, in our study, the direct methods using a straight line demonstrated the best results; this corroborates the findings by Meylemans et al, who compared measurement methods using a straight line or multiple straight lines [19].…”
Section: Discussionsupporting
confidence: 90%
“…In the recent study, different methods were used to measure the tumor distance from the anal verge on sagittal MRI. Although the majority of research groups have used multiple straight lines from the anal verge along [6,18,19] or not along [2,[20][21][22][23][24] the anorectal centerline, others have used a single straight line [19,25]. Thus, there is no clear consensus on the measurement of tumor distance, and no prospective study has compared these methods.…”
Section: Introductionmentioning
confidence: 99%
“…These authors used the anal verge as a landmark and their levels of agreement were –15.7 cm to 4.7 cm, clearly showing a large variability between the measurements. 19 In regular clinical practice, flexible endoscopes are used that may bend and thereby add a few centimeters to the true distance. Furthermore, the distance hallmarks on the endoscopes are spaced 5 cm apart, which may lead to mistakes in measuring distances.…”
Section: Discussionmentioning
confidence: 99%
“…Only one small study by Paparo et al, including 66 patients, concluded that MRI measurements of rectal tumor height correlated well with rigid proctosigmoidoscopy. These authors used the anal verge as a landmark and their levels of agreement were –15.7 cm to 4.7 cm, clearly showing a large variability between the measurements 19 . In regular clinical practice, flexible endoscopes are used that may bend and thereby add a few centimeters to the true distance.…”
Section: Discussionmentioning
confidence: 99%
“…On the sagittal T2W images, APR was identi ed as a thin hypointense linear structure noted along with the superior bladder (men) or uterus (women), which extended inferiorly and posteriorly to the tip of the seminal vesicles in men and to the cul-de-sac in women, after which the posterior extension attached to the anterior rectal wall (Fig. 1A, B) [20]. Unfortunately, not all APRs can be visualized on MRI in clinical practice [4].…”
Section: Introductionmentioning
confidence: 99%